Optimization of Human Resource Management at Ponorogo Halal Center IAIN Ponorogo - Siti Fathonah; Amrul Hinung Prihamayu (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: As one of the LP3H, Ponorogo Halal Center (PHC) IAIN Ponorogo accommodates more than 500 PPH assistants. However, of that number, only around 100 assistants actively provide assistance. This is because the companions have different backgrounds and professions, so being a companion is not their main focus. Therefore, good human resource management is needed by PHC IAIN Ponorogo so that all PPH assistants can be active and have good performance. Research Methods: The method used in this research is a qualitative method with a case study approach, namely aiming to provide a detailed description of a particular case or phenomenon. With data collection techniques through documentation and interviews with 4 PHC administrators and 7 PPH assistants under the auspices of PHC using inductive data analysis techniques. Conclusion: The conclusion of this study shows that the human resource management that has been carried out by PHC IAIN Ponorogo in terms of procurement, development, compensation, and maintenance has been good. Meanwhile, the integration aspect between assistants and between assistants and PHC has not been implemented optimally. This has an impact on the number of active assistants which is still small, which is around 100 people out of a total of 500 assistants and the lack of participation of assistants when there are meetings or coordination activities. Therefore, there needs to be a program or activity that aims to increase integration or a sense of unity between assistants and PHC IAIN Ponorogo and integration between PPH assistants. In addition, the aspect of dismissal at PHC IAIN Ponorogo has not been implemented because the authority to revoke the assistant registration number is directly from BPJPH.